1, 3‐Bis(2′‐hydroxyethyl)imidazolium ionic liquids: correlating structure and properties with anion hydrogen bonding ability. (5th September 2013) - Deng, Feng; Reeder, Zachary K.; Miller, Kevin M.
<x xml:space="preserve">Abstract</x> A series of 1, 3‐bis(2′‐hydroxyethyl)imidazolium ionic liquids is reported where 1H NMR chemical shift values and thermal stabilities (Td), as determined by thermogravimetric analysis, are correlated with the hydrogen bonding capability of various anions ([Cl−], [Br−], [CF3CO2−], [NO2−], [MsO−], [NO3−], [TfO−], [BF4−], [NTf2−], and [PF6−]). Use of anions with the strongest hydrogen bonding capability, such as chloride [Cl−], bromide [Br−], and trifluoroacetate [CF3CO2−], led to the furthest observed downfield chemical shift values in DMSO‐d6 and the poorest thermal stabilities ([CF3CO2−] < 200 °C). Thermal stabilities in excess of 350 °C and upfield chemical shift values were observed for ionic liquids, which employed the weakly coordinating triflate [OTf−], tetrafluoroborate [BF4−], or bis(trifluoromethylsulfonyl)imide [NTf2−] anion. Optimized structures of selected ionic liquids, as determined by density functional theory calculations at the B3LYP/6‐31G + (d, p) level, indicated that the anion preferred to be located above the imidazolium ring and in close proximity to the hydroxyl groups. Calculated dissociation energies (ΔE) and a comparison of key bonding distances (C2―H, (C2)H···X, O―H, and (O)H···X) also confirmed this structural preference. Copyright © 2013 John Wiley & Sons, Ltd.